(untitled) (REMUNOM, 2023)
INTRODUCTION: Changes in dietary patterns and lifestyle have led to an increase in the prevalence of overweight and obesity, considered one of the main risk factors for chronic non-communicable diseases. Given this, the objective of the study is to synthesize the effects of the Brazilian population’s income on food consumption at home and outside it and their exposure to chronic non-communicable diseases. METHODOLOGY: This is an integrative literature review, carried out in April and May 2023 in the MEDLINE and LILACS databases. A search was carried out by crossing descriptors and their combinations in Portuguese and English, in addition to using the Boolean operator “and”. Articles associated with the proposed theme were included, published between 2019 and 2023, studies carried out with the Brazilian population and with texts in Portuguese and English. RESULTS: Income had an impact on the practice of healthy eating habits, especially among low-income individuals, with a decline in the consumption of basic foods in Brazilian meals and an increase in the consumption of ultra-processed foods at home and outside. Excess weight prevailed in regions that, despite having a significant consumption of fresh or minimally processed foods, socioeconomic factors interfere with access to healthy foods, exposing individuals to chronic diseases and non-communicable diseases. CONCLUSION: Economic issues among the Brazilian population influenced the consumption of foods of inadequate nutritional quality both at home and abroad.